ANALISIS HUKUM TERHADAP PERLINDUNGAN DANA NASABAH PADA BANK - Hasaziduhu Möhö; Antonius Ndruru; Yonathan Laowö (JURNAL MathEdu (Mathematic Education Journal), 2023)
Discourse on rights and obligations remains relevant for discussion, especially when it comes directly to the need for guarantees and/or protection of interests. Various efforts were made through the formulation of boundaries between the rights and obligations of each person, what must be done and what should not be done, so that in the end a balance between rights and obligations can be created in harmony. The use and exercise of rights must be in a reasonable measure and in measurable actions and not conflict with the interests (rights) of other people. In this case the very strategic role and responsibility of the bank always pays attention to the comfort factor and security guarantees of the funds deposited by the community (the bank). As a deposit fund, the community must be given adequate and easy access services to store, retrieve, utilize and use the funds that have been deposited. Therefore, information and promotion about the existence of a bank must be able to give and increase the level of public trust, especially the community as depositors on a small scale. The type of research used in this paper is normative legal research, which seeks to examine legal principles or norms, legal systematics, levels of legal synchronization, comparative law and legal history. Whereas for the sake of and to maintain the trust of bank customers and the existence of legal protection for depositors, banks must always be guided by the application of the precautionary principle in carrying out their business and activities; Emphasizing the Maximum Credit Limit without exception. There is sufficient transparency of information that is easily understood or understood by the general public; The Government's role is still very much needed in efforts to provide guarantees to depositors, especially when the bank concerned has its business license revoked and/or is liquidated; It is necessary to emphasize the imposition of sanctions for anyone who violates the law, especially from banks and large-scale depositors. There needs to be a rule of law that specifically favors depositors on a small scale; Sanctions for anyone who violates the law, especially from banks and depositors on a large scale, need to be tougher.